2020
DOI: 10.1016/j.adro.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Lymph Node Failure in Patients With Recurrent Prostate Cancer Postradical Prostatectomy and Implications for Salvage Therapies

Abstract: Purpose There is increasing use of radical prostatectomy to treat patients with high-risk prostate cancer. This has contributed toward a pathologic stage migration, and a greater number of patients are subsequently being diagnosed with biochemical failure. There is increasing use of advanced imaging techniques in the setting of biochemical failure, including positron emission tomography-computed tomography (PET-CT). Methods and Materials This critical literature review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 95 publications
(161 reference statements)
0
10
0
Order By: Relevance
“…Translating this finding to the radiation-oncology community implies the use of vascular anatomy instead of the bony anatomy and inclusion of common iliac nodes, which has also been proposed in published reviews. 16,54 This increasing knowledge also led to an adaptation in the RTOG delineation guidelines 55 for pelvic nodal areas. These guidelines stress the importance of the upper (should include common iliac arteries and veins) and lower delineation limits (should include presacral nodes to the bottom of the third sacral vertebra).…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Translating this finding to the radiation-oncology community implies the use of vascular anatomy instead of the bony anatomy and inclusion of common iliac nodes, which has also been proposed in published reviews. 16,54 This increasing knowledge also led to an adaptation in the RTOG delineation guidelines 55 for pelvic nodal areas. These guidelines stress the importance of the upper (should include common iliac arteries and veins) and lower delineation limits (should include presacral nodes to the bottom of the third sacral vertebra).…”
Section: Interpretation Of Trial Resultsmentioning
confidence: 99%
“…9 An exploratory post-hoc analysis of the Medical Research Council PR07 trial 13 confirmed that there was no benefit of whole pelvis radiotherapy. Reasons for this finding might not necessarily be due to the absence of a benefit, but might be the result of incorrect patient selection (in patients with low risk and positive pelvic nodes the benefit of whole pelvis radiotherapy is often absent), [4][5][6]8,9,11,[14][15][16] inadequate treatment volume definition (not all pelvic nodal regions at risk were considered and consequently not irradiated), 2,4,5,7,[9][10][11]14,15,17,18 inappropriate technology used, 3,10,19 an insufficient dose, 4,[10][11][12]14,15,17,19,20 and inadequate use of concomitant and adjuvant androgen deprivation therapy. 9,11,17,20,21 In 2014, Dirix and colleagues 2 published a systematic review on this issue, analysing seven contemporary retrospective studies from 2006 to 2011 on elective pelvic radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The recent proPSMA randomised study reported that PSMA PET-CT had a greater accuracy compared to conventional imaging with CT and bone scan in the primary setting (92% vs 65%) ( 81 ). PSMA PET-CT also has superior performance characteristics for the detection of distant metastasis in the setting of biochemical failure compared to other PET tracers ( 82 ). Nevertheless, the clinical significance of detecting and treating small volume local recurrence at low PSA levels remains uncertain and may risk additional toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Through improved characterization of recurrent prostate cancer, PSMA-targeted PET/CT has shown significant impact on management decisions, such as by identifying patients with recurrence confined to the prostate or pelvic nodes [179,180]. At a PSA value of less than 0.5 ng/mL, PSMA-PET/CT detects lymph node metastases in approximately 20 % of patients [181].…”
Section: Salvage Radiotherapy In Recurrent Prostate Cancermentioning
confidence: 99%